(3QLGd GdTjN GdWhSjs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3eMeO Hf eMSf GdMSfj Gdbejs)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hGdUdGI Ydi NjQ Ndbg eMeO hBdg GdWGgQjf(B...(3CeG HYO aEfj bO CLHJ Edi(B...(3ef LeY cJGH jTJed Ydi CSeGA GdQLGd GdPjf QhhG Yf GdfHj (B- (3Udi Gddg Ydjg hSde hBdg (B- (3hYf GdCFeI(B...s
(3BNQgG (B:s
...(3HGH GdfSGA aGWeI HfJ gGQhf Hf ehSi Hf GdaQGJ Qhi YfgG GdJdYcHQj bGdJ SeYJ LOj ehSi Hf GdaQGJ jbhd MOKfj eMeO Hf CHj YejQ HcJGH CHj YHO Gddg Hf Ydj(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:6(3,U(B84s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B225s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs